Ganti Rugi Akibat Wanprestasi dalam Perjanjian Jual Beli Online di Tinjau dari Pasal 19 Undang-undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Aan Handriani; Endang Prastini (Program Studi Hukum Universitas Pamulang, 2020)
In activities that connect parties to carry out commercial activities such as buying and selling and carried out via the Internet or on line, many people now enjoy it because it is considered more practical. However, the potential for default is greater than face-to-face transactions. The research method used by the author is a normative juridical research method. Based on the results of the research, it is concluded that the validity of the sale and purchase agreement via online is the same as the validity of the conventional agreement, namely that the provisions contained in Article 1320 of the Civil Code concerning the legal terms of the agreement must be fulfilled. Legal protection for consumers shopping on line can be provided in terms of legal certainty as stipulated in the laws and regulations governing online shopping, namely Law Number 19 of 2016 and Law Number 8 of 1999 concerning Consumer Protection.